2015
DOI: 10.1111/1541-4337.12129
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Guide to Gluten: How Modern Genotypes and Processing Impact Wheat Sensitivity

Abstract: The role of wheat, and particularly of gluten protein, in our diet has recently been scrutinized. This article provides a summary of the main pathologies related to wheat in the human body, including celiac disease, wheat allergy, nonceliac wheat sensitivity, fructose malabsorption, and irritable bowel syndrome. Differences in reactivity are discussed for ancient, heritage, and modern wheats. Due to large variability among species and genotypes, it might be feasible to select wheat varieties with lower amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 217 publications
(349 reference statements)
1
78
0
19
Order By: Relevance
“…The results are consistent with those reported by Kucek et al (2015) who found that, wet gluten content of different varieties of wheat was ranged from 21.3 to 32.3%, while dry gluten content was ranged from 8.44 to 11.7%. Concerning to the gluten index value, it was recorded 88.9 and 95.05% for non-GMW and GMW flour samples, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The results are consistent with those reported by Kucek et al (2015) who found that, wet gluten content of different varieties of wheat was ranged from 21.3 to 32.3%, while dry gluten content was ranged from 8.44 to 11.7%. Concerning to the gluten index value, it was recorded 88.9 and 95.05% for non-GMW and GMW flour samples, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…However, these approaches may be used to develop celiac-safe wheat; this remains a formidable challenge due to the complex multigenic control of gluten protein composition, besides the requirement of acceptable technological properties for bread and pasta-making [19,20].…”
Section: Gluten Proteinsmentioning
confidence: 99%
“…Current knowledge about the pathogeneses of CD has been associated with the long chain and amino acid composition of the peptides generated during gastrointestinal digestion of the gluten proteins [20]. Due to the lack of lysine and arginine residues in gluten proteins, the action of the proteases, such as trypsin, but also chymotrypsin and pepsin, is very difficult, making the proteolysis practically ineffective.…”
Section: Celiac Disease (Cd)mentioning
confidence: 99%
“…The impact of wheat processing methods on wheat sensitivity (including celiac disease, wheat allergy, NCWGS, fructose malabsorption, and irritable bowel syndrome) has been recently reviewed [31]. Authors recalled that ''modern processing can differ from traditional methods by (1) using ungerminated grain, (2) replacing long and diverse fermentation with fast-acting baker's yeast (Saccharomyces cerevisiae), (3) using nonacidic dough, (4) adding extracted wheat proteins and inulin to food products, and (5) focusing on refined white flour" (pages 293-294) [31].…”
Section: Previous Argumentsmentioning
confidence: 99%
“…Authors recalled that ''modern processing can differ from traditional methods by (1) using ungerminated grain, (2) replacing long and diverse fermentation with fast-acting baker's yeast (Saccharomyces cerevisiae), (3) using nonacidic dough, (4) adding extracted wheat proteins and inulin to food products, and (5) focusing on refined white flour" (pages 293-294) [31].…”
Section: Previous Argumentsmentioning
confidence: 99%